2006
DOI: 10.1002/j.2158-1592.2006.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Internal and Downstream Integration and Its Association With Performance

Abstract: The authors study how internal and downstream integration and their interaction affect logistical and financial performance within the firm. The results indicate that internal and downstream integration and their interaction affect logistical performance — that is, the higher the internal integration, the stronger the relationship of downstream integration with logistical performance. The results also suggest that logistical performance directly predicts financial performance. The results suggest that superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
212
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(238 citation statements)
references
References 11 publications
20
212
1
5
Order By: Relevance
“…It was also the most contributing practice that affected SC efficiency. Our results consistent with other studies that pointed to the key role of internal integration for superior SC performance (e.g., Germain & Iyer, 2006;Droge et www.ccsenet.org/ibr International Business Research Vol. 7, No.…”
Section: Resultssupporting
confidence: 92%
“…It was also the most contributing practice that affected SC efficiency. Our results consistent with other studies that pointed to the key role of internal integration for superior SC performance (e.g., Germain & Iyer, 2006;Droge et www.ccsenet.org/ibr International Business Research Vol. 7, No.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have only partially studied this relationship, as they tested the impact of SCM as an unidimensional construct on a multidimensional operational performance (Fynes et al, 2005;Shin et al, 2000) or the impact of the SCM on different competitive priorities (Carr & Kaynak, 2007;Droge et al,. 2004;Germain & Iyer, 2006;Vickery et al, 2003). Findings suggested that SCM impacted positively the operational performance as a whole and all the competitive priorities, providing support for the cumulative capabilities perspective.…”
Section: Discussionmentioning
confidence: 81%
“…Some authors found there is no direct relationship between internal integration and the operational performance of the manufacturer (Koufteros et al 2005;Gimenez and Ventura 2005); others found that there is a positive relationship between the internal integration and the operational performance, including the performance on process efficiency (Saeed et al 2005) and logistics service (Stank et al 2001;Germain and Iyer 2006).…”
Section: Relationship Of Sci To Opmentioning
confidence: 99%